Teen Substance Abuse Problem Based Learning (PBL) - Maurice Clifton (Association of American Medical Colleges, 2009)
Abstract Introduction Managing an adolescent patient with substance use and abuse is complex especially when parents are involved. We created this problem-based learning (PBL) exercise to facilitate teaching about substance use and abuse in an adolescent during a 1-hour rounds-type format within a clinical curriculum. Methods This resource contains a facilitator guide that outlines the case and provides question prompts which may be used to guide the students' experience of the case. A learner version of the case and a handout containing useful reference information are also provided. This group works through each page followed by a very short summary of the learning points that are on the facilitator copy. It is important that the facilitator has a basic understanding of talking with adolescents and is comfortable with the PBL format. Results This case has been used multiple times. No formal studies have been done, but it has been used multiple times with a pediatric inpatient team made up of multiple levels of learners. Informal feedback has been uniformly positive supporting that the case is realistic, useful, and practical. Discussion This case is appropriate for both undergraduate and graduate medical education settings and has been successful when utilized with a pediatric inpatient team made up of multiple levels of learners. While used in a rounds-type format it can be adapted to other PBL or case-based formats.